THE MONITORING ROLE OF NON-EXECUTIVE DIRECTORS IN VIETNAM FROM A RETURN-VOLATILITY PERSPECTIVE - Tho To, Anh; Tuan Tran, Quoc; Siem Tran, Thi; Phong Thai, Kim; Thu Hong Ho, Thi (Economic Annals, 2020)
This study examines the relevance of board independence to stock return volatility for a sample of 160 compa-nies listed on the Vietnamese stock market over ten years (2008–2017). After control-ling for potential endogeneity, we find that the presence of non-executive directors on the board tends to increase firm risk. The results indicate that non-executive direc-tors do not play a supervisory role under the agency theory. Our findings remain ro-bust when we apply alternative measures of the dependent variable.